Molten material movement trajectories and geometries in the ultrasonic vibration-assisted laser directed energy deposition - Sarower Kabir; Bo Zhao; Weilong Cong (Results in Engineering)
Among laser additive manufacturing (LAM) technique laser directed energy deposition (LDED) method has many benefits, including versatility, ability to use a wide variety of materials, and efficiency in material utilization and waste reduction. Popular areas of applications of LDED include aerospace and biomedical engineering, where complex shapes that would be challenging to produce using conventional methods. But the LDED method is associated with issues such as porosity, lack of fusion, and inhomogeneity in microstructure and material distribution. Incorporating ultrasonic vibration- assisted (UV-A) LDED can greatly improve the fabricated components' quality while reducing the occurrence of these defects. To comprehensively understand the defect evolution and mechanical properties during the LDED process, it is imperative to analyze the molten materials movement within the fabricated part. But the research in molten material trajectories during the LDED process is still insufficient. In addition, the effects of ultrasonic vibration should be investigated. In the present research, to understand the mechanism of ultrasonic vibration on material movement and distribution along the deposition direction and adjacent track, an alternative material (17–4 PH Fe-Cr) was attached to the top of the substrate to chase the trajectories of the material. The result illustrated that the UV-A LDED process led to uniform and homogenous distribution of material inside the molten pool along the deposition direction. An approximately 10 % increase in molten pool geometry was observed accompanied by a reduction in balling effects and decrease in grain size by 15 % which led to increases in microhardness of the fabricated components.